Compulsão alimentar, imagem corporal e qualidade de vida em crianças e adolescentes obesos - Monica Maria de Oliveira Melo (2011)
OBJECTIVE: This studys aim was to discuss the challenge of diagnosis of binge eating in children and adolescents by comparing two diagnostic instruments, the Binge Eating Scale (BES) and a semi-structured interview specially prepared for this study and based on the concept of loss of control over eating. Another goal of this study was to evaluate body satisfaction and body image on obese children and adolescent with binge eating, since some studies have suggested that concerns about body image and weight should be included as criteria for binge eating. This study also evaluated quality of life and bullying in these patients. METHODOLOGY: descriptive cross-sectional study with a sample of 33 obese children and adolescent from private health system. Only patients with weight higher than percentile 97 of BMI were selected before treatment starts and before using of any medication or dieting. The instrument BES was applied to diagnose binge eating according to DSMs criteria and the semi-structured interview was also applied based on the newer literature criteria that considers loss of control over eating the central point for the diagnosis of binge eating. The Body Shape Questionnaire (BSQ) and the Body Figure Silhouette were used to diagnose body dissatisfaction and body image. The Pediatric Quality of Life Inventory (PedsQL) and the questionnaire about Bullying from Kidscape were also applied. Other variables like sex, age, BMI, obese familiar and practice of physical exercise were evaluated. RESULTS: BES identified 14 patients as binge eaters and the interview identified 18 patients, with good concordance between the two instruments. However, all patients identified as binge eaters by the interview but not identified by BES answered negatively to the questions about the amount of food intake. In the 18 patients identified as binge eaters, 10 were not satisfied with their bodies and 8 were satisfied and there were no statistical association between the eating disturbance and body dissatisfaction in this sample. Body satisfaction, quality of life and bullying were associated with BMI with statistical significance. CONCLUSION: results showed that some patients relating loss of control over eating may not be identified by DSMs criteria for not filling the criteria of great amount of food intake. It was not observed in this sample association between binge eating and corporal dissatisfaction, suggesting that maybe there are two types of binge eaters, those in which binge episodes occur as a response to obsessive thoughts about body shape and weight and those with more impulsive behavior not related to concerns about weight or shape. Body dissatisfaction, worse quality of life and bullying victimization were associated with higher BMIs, enhancing the necessity of multiprofessional and careful evaluation of these patients.